Accumulation of vitamin C and sugars in wild rose hips of Karaganda region - Tyrzhanova, S.S.; Mussina, R.T. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The study of wild fruit plant populations has a great potential in the selection of species and forms promising in terms of a number of economically valuable traits for introduction and industrial cultivation. Local species are more resistant to local climatic conditions and composition of pathogens. The aim of the study was to evaluate the accumulation of sugars and vitamin C in fruits of 3 wild rose hips collected in Karaganda region. The quantitative accumulation of vitamin C varied from 0.87 to 1.85 %, the sum of sugars from 6.8 to 15.8 %. Analysis of fruits for accumulation of sugars and vitamin C showed that Rosa majalis from the Nura River floodplain, Rosa spinosissima from Komissarovka tract, Rosa acicularis from the vicinity of Karagaily settlement are promising for selection in the introduction experiment.
Қарағанды облысындағы жабайы итмұрында С витамині мен қанттың жинақталуы
Накопление витамина С и сахаров в дикорастущих шиповниках Карагандинской области
Keywords: plants of Rosa genus; fruits; Karaganda region; vitamin C; sugars; quantitative accumulation